PERLINDUNGAN HUKUM TERHADAP KONSUMEN JASA PENGIRIMAN BARANG ONLINE MELALUI DARAT - Fadhil Khalid (2022)
When shipping goods, consumers often need legal protection, and freight forwarders often act against the owner and buyer of the goods. In Indonesia protection for consumers has been regulated in the Consumer Protection Law. From the relevant laws and regulations, namely Law Number 8 of 1999 concerning Consumer protection. The owner of the shipping company must ensure that the vehicle used to transport goods to meet established standards. In doing In this research, the author uses the method of literature study, or legality, which is obtained through the search for library documents or secondary documents that are collected, analyzed, and processed. This study contains theories from the literature or previous reviews. This type of research using secondary data in the form of library data and legal documents in the form of regulations legislation and legal theory. Legal protection for consumers in the use jof transportation asaincludes two types, the first, legal protection prevention (preventive), namely legal protection before a dispute occurs. Second, repressive legal protection, meaning that resolve disputes that arise between consumers and transportation services. Responsibility shipping companies in delivering goods involve the obligation to be able to provide compensation in the event of causing harm to consumers. Business Actors are also prohibited from including The Exenoration Clause or Standart Contract in their agreements. It is hoped that the companies expeditions that transport goods must always provide accountability in accordance with matters regulated in the Law on Consumer Protection. Responsibility transportation companies or companies delivering goods to consumers must be implemented properly and quite in line with the provisions contained in the legislation. So that consumers do not experience losses in using the expedition service.